(untitled) (Research, Society and Development, 2021)
Brazil has favorable environmental aspects for the production of fish, with this, it has shown constant growth. Rio Grande do Sul is a state that has great potential for growth in activity, mainly in the commercialization of fish. However, there are some obstacles that hinder the sale of fish in the state. The present study aimed to identify and characterize the marketing channels used by fish farmers in the northwestern mesoregion of Rio Grande do Sul, to drain their production. The survey was conducted in five municipalities in the northwestern mesoregion, which presented the largest volume of fish traded in 2017, namely: Ajuricaba, Barra Funda, Chapada, Nova Ramada and Tenente Portela. Data collection was carried out between January and March 2020, 64 interviews were conducted, using a semi-structured research script. The results show that the main channels used by fish farmers in the Northwest Mesoregion were the intermediaries and the slaughterhouses. While the short channels, due to the characteristics of the region and production systems, are little used. The study also points out that one of the main difficulties encountered in commercialization is related to the low valuation of the product and the difficulties when receiving for the commercialized product.